Digital platforms and institutional voids in developing countries: The case of ride-hailing markets. (September 2021) - Heeks, Richard; Gomez-Morantes, Juan Erasmo; Graham, Mark; Howson, Kelle; Mungai, Paul; Nicholson, Brian; Van Belle, Jean-Paul
Highlights: Institutional voids – weakness in the institutional functions required by markets – particularly hamper developing countries. Ride-hailing digital platforms can fill these voids and make markets more efficient, effective, complete and formalised. Platform companies also maintain, expand and create institutional voids, and they make markets more unequal. Platform companies create inequality by internalising previously-distributed market functions and power. Ongoing institutional voids need to be filled by informational, state regulatory or worker collectivisation interventions. Abstract: Institutional voids – shortcomings in the institutional functions required by markets – have particularly hampered developing countries. Filling those voids has been widely identified as a strategy for businesses and in this paper we analyse the institutional actions of digital platform companies. Specifically and through primary research, we analyse the impact of e-hailing platforms (Uber, Bolt and EasyTaxi) in Colombia and South Africa on ride-hailing markets characterised by institutional voids. Alongside the void-filling discussed in the literature, we identify three other institutional strategies of these businesses: they also maintain and expand and create institutional voids. The platform companies' institutional work has formed a market that is more efficient, effective, complete and formalised. At the same time, though, they have institutionalised problematic behaviours and significant inequalities. They have done this by internally institutionalising – within the digital platform and in their broader business model – previously-distributed market functions and power. We suggest some practical actions to address the downsides of platformisation through the filling of ongoing voids, and we identify some research priorities for future studies of institutional voids and platforms in developing countries.